2006
DOI: 10.1016/j.epsl.2006.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Revised chronology for late Pleistocene Mono Lake sediments based on paleointensity correlation to the global reference curve

Abstract: Lakes are highly sensitive recorders of climate processes, but are extremely difficult to correlate precisely to ice-core and marine records, especially in the absence of reliable radiocarbon dates. Relative paleointensity (RPI) of Earth's magnetic field is an independent method of correlating high-resolution climate records, and can be applied to both marine and terrestrial sediments, as well as (inversely) correlated to the cosmogenic nuclide records preserved in ice cores. Here we present the correlation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 39 publications
10
68
0
Order By: Relevance
“…Further, the variation of the leachable elements with Mono Lake levels is opposite that found in Owens Lake (Bischoff et al, 1997a,b), consistent with the observations made by Zimmerman et al (2006Zimmerman et al ( , 2011b for calcium carbonate. These results document important differences between these two lakes, discussed below.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Further, the variation of the leachable elements with Mono Lake levels is opposite that found in Owens Lake (Bischoff et al, 1997a,b), consistent with the observations made by Zimmerman et al (2006Zimmerman et al ( , 2011b for calcium carbonate. These results document important differences between these two lakes, discussed below.…”
Section: Resultssupporting
confidence: 84%
“…Leachable Li concentrations also show an excellent agreement with CaCO 3 concentrations throughout the Wilson Creek Formation, which has been previously demonstrated to follow lake level (Zimmerman et al, , 2011b. It also appears to document millennial timescale changes which are not explicitly documented in the much lower resolution lake level curve, but are seen in the CaCO 3 record (Benson et al, 1998;Zimmerman et al, 2006). However, the Li concentrations corresponding to the interval from Ash 8 to the top of the Wilson Creek Formation fail to reflect the extremely high lake at approximately 14 ka.…”
Section: Acid Leachable LI and Lake Levelsupporting
confidence: 55%
“…Given its unique trace-element composition (see Table 1 in Benson et al, 2003), the Carson Sink Bed can be shown to be equivalent to Wilson Creek Ash 15, which was deposited during the Mono Lake magnetic excursion. This implies that the Mono Lake excursion occurred 7 ka after the Laschamp magnetic excursion, and is not equivalent to that excursion as previously suggested by Kent et al (2002) and Zimmerman et al (2006).…”
Section: Gisp2 Calendar Ages Of Tephras In Cores Plc08-1 and Plc92bmentioning
confidence: 72%
“…Nonetheless, the Wilson Creek silts preserve a high-fi delity record of the magnetic fi eld, because they are the result of glacial grinding of the igneous and metasedimentary Sierran bedrock, with no signifi cant chemical weathering and very low organic carbon (Liddicoat and Coe, 1979;Lund et al, 1988;Liddicoat, 1992;Zimmerman et al, 2006). Thus, correlation of a relative paleomagnetic intensity record in the Wilson Creek Formation to well-dated marine records and stacked curves has provided a means to estimate the age of the base of the Wilson Creek Formation.…”
Section: Paleomagnetic Records In the Wilson Creek Formationmentioning
confidence: 95%